Baby Honu's incredible journey - Yee, Tammy (Aiea, Hawaii : Island Heritage, 1997)
The adventures of a baby turtle as he attempts to crawl to the ocean after being born.
New May 2015.
Keywords: Sea turtles -- Juvenile fiction; Hawaii -- Juvenile fiction